PENGARUH VOLUME PERDAGANGAN DAN KAPITALISASI PASAR TERHADAP VOLATILITAS HARGA PADA CRYPTOCURRENCY - Tamara Audry Anandika Syahrir; Tenri Sayu Puspitaningsih Dipoatmodjo; Andi Mustika Amin; Anwar, Anwar; Annisa Paramaswary Aslam (Bajang Institute, 2025)
This research aims to examine the impact of trading volume and market capitalization on price volatility in the cryptocurrency market, while also identifying the direction and significance of each variable's influence. The study employs a quantitative methodology. Data were obtained through documentation of monthly historical cryptocurrency records. The sample comprises the five leading cryptocurrencies ranked by market capitalization: Bitcoin, Ethereum, Ripple, Tether, and Binance Coin. Data analysis utilized panel regression techniques to investigate the effect of independent variables (trading volume and market capitalization) on the dependent variable (price volatility). The findings reveal that trading volume demonstrates a positive and significant effect on cryptocurrency price volatility, suggesting that increased trading activity escalates price fluctuations. In contrast, market capitalization exhibits a negative and significant effect on price volatility, indicating that assets with larger market capitalization experience lower price volatility